Role of SNAREs in Neurodegenerative Diseases - Margiotta, Azzurra (Cells, 2021)
Neurodegenerative diseases are pathologies of the central and peripheral nervous systems characterized by loss of brain functions and problems in movement which occur due to the slow and progressive degeneration of cellular elements. Several neurodegenerative diseases are known such as Alzheimer's disease, Parkinson's disease and amyotrophic lateral sclerosis and many studies on the molecular mechanisms underlying these pathologies have been conducted. Altered functions of some key proteins and the presence of intraneuronal aggregates have been identified as responsible for the development of the diseases. Interestingly, the formation of the SNARE complex has been discovered to be fundamental for vesicle fusion, vesicle recycling and neurotransmitter release. Indeed, inhibition of the formation of the SNARE complex, defects in the SNARE-dependent exocytosis and altered regulation of SNARE-mediated vesicle fusion have been associated with neurodegeneration. In this review, the biological aspects of neurodegenerative diseases and the role of SNARE proteins in relation to the onset of these pathologies are described.
Keywords: SNARE Proteins; syn1; Humans; neurodegenerativní nemoci; proteiny SNARE; fúze membrán; lidé; Alzheimer’s disease; zvířata; Membrane Fusion; exocytóza; Synaptic Transmission; Parkinson’s disease; nervový přenos; VAMP2; ALS; Exocytosis; SNAP-25; neurodegenerative disease; SNAREs; Neurodegenerative Diseases; Animals